Rift-related paleogeography of the European margin in the Eastern Alps (Central Tauern Window) - Groß, Philip; Pleuger, Jan; Handy, Mark R. (Swiss journal of geosciences, 2022)
Continent-derived tectonic units in the Tauern Window of the Alps exhibit stratigraphic and structural traces of extension of continental margins eventually leading to the opening of the Alpine Tethys. In this study, we reassess lithostratigraphic data from the central part of the Tauern Window to reconstruct the post-Variscan evolution of this area, particularly the rift-related geometry of the European continental margin. The lithostratigraphy of the Alpine nappes reflects systematic variations of the structure of the European margin. The lowest tectonic units (Venediger nappe system, Eclogite Zone and Trögereck Nappe) are characterized by a thick succession of arkose-rich Bündnerschiefer-type sediments of probably Early Cretaceous age that we interpret as syn-rift sequence and which stratigraphically overlies thinned continental basement and thin pre-rift sediments. In contrast, the highest tectonic unit derived from Europe (Rote Wand Nappe) preserves a thick pre-rift sedimentary sequence overlying thinned continental basement, as well as a thick syn- to post-rift succession characterized by turbiditic Bündnerschiefer-type sediments of probable Cretaceous age. These observations point towards a highly segmented structure of the European rifted margin. We propose that this involved the formation of an outer margin high, partly preserved in the Rote Wand Nappe, that was separated from the main part of the European margin by a rift basin overlying strongly-thinned continental crust. The along-strike discontinuity of the Rote Wand Nappe is proposed to reflect the lateral variation in thickness of the outer margin high that resulted from margin-parallel segmentation of the European continental crust during highly oblique rifting antecedent to the opening of Alpine Tethys.
Gesehen am 10.05.2023